Enhancement of biogas potential of primary sludge by co-digestion with cow manure and brewery sludge - Nansubuga, Irene; Banadda, Noble; Babu, Mohammed; Vrieze, Jo De; Verstraete, Willy; Rabaey, Korneel (International Journal of Agricultural and Biological Engineering, 2015)
Anaerobic digestion (AD) has long been used to treat different types of organic wastes especially in the developed world. However, organic wastes are still more often considered as a waste instead of a resource in the developing world, which contributes to environmental pollution arising from their disposal. This study has been conducted at Bugolobi Sewage Treatment Plant (BSTP), where two organic wastes, cow manure and brewery sludge were co-digested with primary sludge in different proportions. This study was done in lab-scale reactors at mesophilic temperature and sludge retention time of 20 d. The main objective was to evaluate the biodegradability of primary sludge generated at BSTP, Kampala, Uganda and enhance its ability of biogas production. When the brewery sludge was added to primary STP sludge at all proportions, the biogas production rate increased by a factor of 3. This was significantly (p < 0.001) higher than observed gas yield (337±18 mL/(L•d)) in the control treatment containing (only STP sludge). Co-digesting STP sludge with cow manure did not show different results compared to the control treatment. In conclusion, Bugolobi STP sludge is poorly anaerobically degradable with low biogas production but co-digestion with brewery sludge enhanced the biogas production rate, while co-digestion with cow manure was not beneficial. Keywords: wastewater treatment, co-digestion, cow manure, brewery, primary sludge, biogas, energy recovery DOI: 10.3965/j.ijabe.20150804.1616 Citation: Nansubuga I, Banadda N, Babu M, De Vrieze J, Verstraete W, Rabaey K. Enhancement of biogas potential of primary sludge by co-digestion with cow manure and brewery sludge. Int J Agric & Biol Eng, 2015; 8(4): 86－94.